Study on the Long-Term Performance and Efficiency of Single-Well Circulation Coupled Groundwater Heat Pump System Based on Field Test - Zhu, Ke; Zeng, Yifan; Wu, Qiang; Xu, Shengheng; Tu, Kun; Liu, Xiaoxiu (Frontiers in Earth Science, 2021)
Although buildings are often heated and cooled by single-well circulation coupled groundwater heat pump systems, few studies have evaluated the long-term performance of these systems. Therefore, the present study investigated the performance of these systems by analyzing the efficiency and energy consumption using 4 years of operating data. The results indicate that the coefficient of performance (COP) of the system gradually decreases because of thermal breakthrough or an accumulation of cold. In addition, the sealing clapboards could effectively slow down thermal breakthrough. In addition, compared with the heating period, the COP of the heat pump unit (HPU) and system increases, and its energy consumption decreases in the cooling period. It was also found that partial heat loss occurs when water from the single-well circulation outlet penetrates the main pipeline. Moreover, the heat-exchange efficiency of a single HPU exceeds that of multiple HPUs, and the COP of a HPU decreases during operation with increasing indoor temperature. Accordingly, we improved the performance of system by increasing the underground heat storage. Herein, we focus on optimizing the system design during long-term operation, which includes taking steps such as lengthening the sealing clapboards, using insulated pipes, discharging the remaining water and adding intelligent control devices.